Provenance of Cenozoic Sediments in the Xining Basin Revealed by Nd and Pb Isotopic Evidence: Implications for Tectonic Uplift of the NE Tibetan Plateau. (31st October 2019) - He, Zhilin; Guo, Zhengtang; Yang, Fan; Sayem, Abu Sadat Md; Wu, Haibin; Zhang, Chunxia; Hao, Qingzhen; Xiao, Guoqiao; Han, Long; Fu, Yang; Wu, Zhipeng; Hu, Bin
Abstract: Constraining the uplift of the northeastern Tibetan Plateau (NETP) is critical for growth models of the plateau and tectonic‐climatic interactions during the Cenozoic. The sequence of early Eocene (53 Ma)‐early Miocene (16 Ma) clastic sediments deposited in the Xining Basin provides insights into the uplift of the NETP. We used Nd‐Pb isotopic composition of the Cenozoic sediments in the Xining Basin to trace sediment sources and hence to infer uplift of the NETP. Provenance analysis indicates that the Qilian Shan was possibly the source area before ~50 Ma; the West Qinling became the main source area during ~50–39 Ma; and the West Qinling, Qilian Shan, and Laji Shan probably became source areas during ~39–30 Ma. During ~30–16 Ma, the sediments comprised a two‐end‐member mixture of detrital materials from the Laji Shan and the Qilian Shan, whereas detrital inputs from the Qilian Shan increased after ~22 Ma. Combined with previous studies, our inferred provenance history suggests that (1) part of the Qilian Shan possibly existed before ~50 Ma; (2) the West Qinling was uplifted since ~50 Ma; (3) part of the Laji Shan was uplifted during ~39–30 Ma, and the entire Laji Shan was probably uplifted since ~30 Ma, separating the Xining from Xunhua‐Linxia basins; and (4) the Qilian Shan was uplifted during the early Miocene, which together with climate change caused erosion and provenance changes. These results suggest that the NETP was uplifted since the early Cenozoic and sizeable parts of the NETP were probably uplifted by the early Miocene. Key Points: Provenance history of the central part of Xining Basin can be divided into three major intervals: ~53–39, ~39–30, and ~30–16 Ma The Qilian Shan, West Qinling, and Laji Shan were source areas, whereas the Songpan‐Ganzi terrane and East Kunlun were not significant sources Tectonic uplift of the NETP occurred since the early Cenozoic, and sizeable parts of the NETP were probably uplifted by the Early Miocene